2018
DOI: 10.1542/peds.2018-2119
|View full text |Cite
|
Sign up to set email alerts
|

Being Overweight or Obese and the Development of Asthma

Abstract: Adult obesity is linked to asthma cases and is estimated to lead to 250 000 new cases yearly. Similar incidence and attributable risk (AR) estimates have not been developed for children. We sought to describe the relationship between overweight and obesity and incident asthma in childhood and quantify AR statistics in the United States for overweight and obesity on pediatric asthma. METHODS: The PEDSnet clinical data research network was used to conduct a retrospective cohort study (January 2009-December 2015)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
71
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 49 publications
1
71
0
5
Order By: Relevance
“…Obese children have nearly a one third higher risk of developing asthma compared with children of healthy weight, a retrospective US study1 has found.…”
mentioning
confidence: 99%
“…Obese children have nearly a one third higher risk of developing asthma compared with children of healthy weight, a retrospective US study1 has found.…”
mentioning
confidence: 99%
“…An increase in the prevalence of childhood obesity over the past several decades has identified its myriad effects and contribution to chronic pediatric diseases, including asthma. While initial cross‐sectional studies identified an association between obesity and asthma, prospective studies, and more recently, meta‐analyses, have consistently found obesity to be an independent predictor of asthma . Overweight/obese children have a relative risk of 1.2 to 1.8 for incident asthma .…”
Section: Obesity and Asthma: A Causal Associationmentioning
confidence: 99%
“…While initial cross‐sectional studies identified an association between obesity and asthma, prospective studies, and more recently, meta‐analyses, have consistently found obesity to be an independent predictor of asthma . Overweight/obese children have a relative risk of 1.2 to 1.8 for incident asthma . This association varies by sex .…”
Section: Obesity and Asthma: A Causal Associationmentioning
confidence: 99%
See 2 more Smart Citations